“BA-TPF”: A Novel Approach Towards Regression Test Case Optimization - Dalal, Sandeep; r, Sudhi; Solanki, Kamna (International Journal of Engineering and Technology, 2026)
One of the most critical and expensive segment of software development is software testing. It is practically not feasible to conduct exhaustive testing on any software system due to cost and time constraints. Moreover, amendments and modifications in a software for the purpose of fixing failures is inevitable. Therefore, one can never guarantee that a software has been thoroughly tested. Testing the whole software system exhaustively by running the entire set of test cases after every modification is near to impossible. Hence, the software system is tested by running the optimized test suite for minimizing the cost and effort without compromising the quality of the test suite in terms of uncovering faults and providing better coverage based on many parameters. This paper presents a novel technique “BA-TPF” for multi-objective test suite optimization for enhancing path coverage with minimized repetition ratio and minimized test suite size.